MONITORING CONTAMINATION OF THE ENVIRONMENT WITH TOXOCARA EGGS IN KHARKIV REGION - Замазій Т. М. (World of Medicine and Biology, 2014)
The article presents the results of the sanitary-parasitological monitoring of soil as to the toxocara eggs contamination in Kharkiv region. Studies have shown that the average level of soil contamination in rural areas is not much different from the city. The most contaminated soil around child care, private households containing dogs and places of public recreation.